Review of studies of blockchain technology effects on the shipping industry - Kelly Gerakoudi-Ventouri (Journal of Shipping and Trade (JST), 2022)
Decision-making is a prolific research area in the internet era, which has propelled globalization and the virtual elimination of many country border barriers. However, effective decision-making in the shipping industry is a time consuming and often complicated process. Digital evolution has provided new innovative organizational operation methods. Blockchain technology - a basic component of the Fourth Industrial Revolution - is one such innovation that promises to alter the process of decision-making. However, only a few academic studies have explored the decision-making aspect of blockchain technology. Moreover, there is a dearth of comprehensive research on how blockchain affects decisions in the shipping industry. This study explored how this novice technology can address issues, such as vast documentation and information asymmetry in the shipping industry. Specifically, grounded theory was used to qualitatively investigate extant practices and examine the potential impact of blockchain technology on decision-making in the shipping industry and the potential of using blockchain technology to emancipate decision-making. The study results indicate that the instant and reliable data-sharing capability of blockchain can significantly impact the shipping industry, while transforming its decision-making processes.
Keywords: 650; Blockchain; Decision-making; Grounded theory; Knowledge transfer; Shipping